ANALISIS PERBANDINGAN HARGA POKOK PRODUKSI METODE VARIABEL COSTING DAN FULL COSTING PADA PRODUKSI SEPATU SLIP ON DAN SNEAKERS: Studi Kasus: UKM Sepatu New Era Krian, Sidoarjo - Maulana Abdillah Azhim; Zainal Arief (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
UKM Shoes New Era is a company that produces Men's Sneakers and Slip On shoes. In the process of making shoes, raw materials and the length of production time play an important role for the running of the company. New Era Shoes UKM is a company whose production is based on orders which greatly influences the calculation of production costs. Shoe production is aimed at fulfilling orders from customers, not fulfilling inventory in the warehouse. These SMEs also still calculate simple cost records and do not systematically calculate the selling price of shoe products, so they cannot know the selling price of a significant product. Based on the results of calculations carried out in this study, the cost of production of each type of shoe product was divided into two calculation methods. For the full costing method, we get Sneakers shoes of Rp. 52,515, - and Slip-on shoe products of Rp. 52,243.-. While the variable costing method obtained Sneakers shoes of Rp. 52,157 and Slip-on shoes of Rp. 51,907, -. Sneakers are priced at Rp. 75,000, -/Pair and Slip On is priced at Rp. 70.000, -/Pair., the researcher made a simple calculation using excel software